Pengaruh Kebiasaan Paparan Radiasi Blue Light terhadap Kelainan Refraksi Mata pada Mahasiswa Fakultas Kedokteran Universitas Airlangga angkatan 2018 - Clevia Levana Herryawan; Indri Wahyuni; Pudji Lestari; Nurwasis Nurwasis (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Refractive disorders are in the third rank of causes of blindness. Refractive disorders are not uncommon among medical students. Exposure to blue light from the device acts as one of the causes of refractive errors. In this modern era, medical students are often exposed to blue light from their devices in their studies. The study was conducted to see the effect of the habit of exposure to blue light radiation on refractive errors. Method: This study was an analytical study with a cross-sectional design. Determination of the research sample using total sampling technique by taking data from all students of the Faculty of Medicine, Airlangga University, class 2018. Results: Of the 83 study subjects, it was found that 62.7% were women, 37.3% were men. 16.9% were less than 19 years old, 51.8% were 19 years old, 22.9% were 20 years old and 8.4% were over 20 years old. The p value between the cylinder relationship with the eye distance to the device is 0.727. P value cylinder relationship with position 0.891. The p value of the cylinder relationship with the duration of the use of the device is 0.140. The relationship between myopia and the distance of the eye to the device obtained a p value of 0.702. The relationship between myopia and position, the p value was 0.382 and the relationship between myopia and duration was p value 0.552. Discussion: The results of this study are in line with previous studies but some are contradictory. The same results were obtained due to the use of the same method. Meanwhile, the results are conflicting due to differences in research methods and also the age of the sample. Conclusion: There is no significant relationship between the habit of exposure to blue light radiation and eye refractive error among students of the Faculty of Medicine, Airlangga University, class 2018. Keywords: Astigmatism, Blue Light, Gadget, Myopia, Radiation, Refraction Abnormalities, Refractive Error